2013
DOI: 10.3389/fnhum.2013.00688
|View full text |Cite
|
Sign up to set email alerts
|

Origins of specificity during tDCS: anatomical, activity-selective, and input-bias mechanisms

Abstract: Transcranial Direct Current Stimulation (tDCS) is investigated for a broad range of neuropsychiatric indications, various rehabilitation applications, and to modulate cognitive performance in diverse tasks. Specificity of tDCS refers broadly to the ability of tDCS to produce precise, as opposed to diffuse, changes in brain function. Practically, specificity of tDCS implies application-specific customization of protocols to maximize desired outcomes and minimize undesired effects. Especially given the simplicit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
269
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(300 citation statements)
references
References 68 publications
13
269
1
4
Order By: Relevance
“…Thus the technique carries promise in being able to evaluate the effects of up-/down-regulating the neuronal excitability of certain brain regions on cognitive functions. However, in general, it should be noted that the exact brain regions affected by tDCS cannot be precisely delineated (Bikson, Name, & Rahman, 2013;Polanía, Nitsche, & Paulus, 2011), and also that the effect sizes are often relatively small in these studies.…”
mentioning
confidence: 99%
“…Thus the technique carries promise in being able to evaluate the effects of up-/down-regulating the neuronal excitability of certain brain regions on cognitive functions. However, in general, it should be noted that the exact brain regions affected by tDCS cannot be precisely delineated (Bikson, Name, & Rahman, 2013;Polanía, Nitsche, & Paulus, 2011), and also that the effect sizes are often relatively small in these studies.…”
mentioning
confidence: 99%
“…NEBS electrode size or montage may impact cortical areas adjacent to the region of interest, resulting in limited focality of the stimulation itself 45,46 . Smaller electrode sizes (emitting electrode in case of tDCS) may limit the widespread and exert more focal effects onto M1, as suggested by modeling studies or software tools; similarly, less distance between electrodes may condense the electrical field 46,47 .…”
Section: Common To Anodal Tdcs and Trnsmentioning
confidence: 99%
“…Smaller electrode sizes (emitting electrode in case of tDCS) may limit the widespread and exert more focal effects onto M1, as suggested by modeling studies or software tools; similarly, less distance between electrodes may condense the electrical field 46,47 . However, the functional focality obtained by task specific activation of particular synapses 11 or networks that are augmented by combining task/training with stimulation could be more crucial 46 : on one hand, functional imaging studies revealed different network changes after unilateral versus bilateral M1 tDCS, or tDCS versus tRNS, respectively 14,15 .…”
Section: Common To Anodal Tdcs and Trnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the specificity of tDCS implies application-specific customization of protocols to maximize desired outcomes and minimize undesired effects. An important issue is that given the simplicity of tDCS and the complexity of brain function, understanding the mechanisms leading to specificity is fundamental to the advancement of tDCS 17 . Moreover, previous studies of our research group using rats have confirmed the immediate and long-lasting effects of repeated tDCS treatment on chronic pain inflammation 18 and hyperalgesia induced by chronic restraint stress models 19 .…”
mentioning
confidence: 99%